Bilateral Three Rooted Mandibular Premolars and Four Rooted Mandibular First and Second Molar: A Rare Anatomical Variant - Shinde, Mrunal Manohar (J Clin Diagn Res, 2016)
The mandibular premolars and molars exhibit wide variations in the form of roots and root canals. A bilateral symmetry of three rooted mandibular first and second premolar and four rooted mandibular first and second molar in a same patient is a rare entity and one such case is presented in this case report.